(untitled) (Research, Society and Development, 2020)
Throughout the history of mankind, there have been several forms of political and economic organizations that have directly influenced the production work mode. Thus, as a product of the social organization, work is indispensable to meet human needs that go beyond survival. In this sense, the objective of this article is to present the social and economic context of the development of the capitalist system, from the main schools of economic thought: Mercantilism, Classical, Neoclassical, Keynesianism, and New Classical. For this, we resort to studies by Oliveira and Gennari (2009); Canterbery (2001); Andrade et al (2020); among others. Regarding the methodological path, we used narrative bibliographic research with a qualitative approach. With this, it was possible to affirm that the exploitation of human labor, the extraction of surplus-value, and the concentration of private property are ideas present in all schools of economic thought. In addition, the study of economic models also made it possible to understand economic interactions, allowing us to understand the relationship between supply and demand. Finally, the data obtained further corroborate the importance of the State in drafting laws that regulate the entire process of production and circulation of products and their insertion in the market.